2019
DOI: 10.1088/1475-7516/2019/07/017
|View full text |Cite
|
Sign up to set email alerts
|

The one-dimensional power spectrum from the SDSS DR14 Lyα forests

Abstract: We present a measurement of the 1D Lyα forest flux power spectrum, using the complete Baryon Oscillation Spectroscopic Survey (BOSS) and first extended-BOSS (eBOSS) quasars at z qso > 2.1, corresponding to the fourteenth data release (DR14) of the Sloan Digital Sky Survey (SDSS). Our results cover thirteen bins in redshift from z Lyα = 2.2 to 4.6, and scales up to k = 0.02 (km/s) −1 . From a parent sample of 180,413 visually inspected spectra, we selected the 43,751 quasars with the best quality; this data set… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
188
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(196 citation statements)
references
References 130 publications
(203 reference statements)
7
188
1
Order By: Relevance
“…This also defines the 1D logarithmic power as ∆ 2 δ F ,1D (k) = (k/π)P δ F ,1D (k), which we compare with observations [55][56][57] in Fig. 8.…”
Section: )mentioning
confidence: 67%
See 3 more Smart Citations
“…This also defines the 1D logarithmic power as ∆ 2 δ F ,1D (k) = (k/π)P δ F ,1D (k), which we compare with observations [55][56][57] in Fig. 8.…”
Section: )mentioning
confidence: 67%
“…7 the ratio of the Lyman-α power spectrum to the linear matter density power spectrum, at redshift z = 3 as a function of the wave number . The data points are observations from [55] (stars), [56] (circles) and [57] (triangles). The solid line is our model.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas for the trigonometric potential there is a bump at large wavenumbers besides the characteristic cut-off, the quadratic and hyperbolic potentials are very similar in their prediction of the structure formation. The data points are from Chabanier et al (2019) and are shown for reference.…”
Section: Linear Density Perturbationsmentioning
confidence: 99%